2021
DOI: 10.1038/s41467-021-25949-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mucosal antibody development and persistence and their relation to viral load and COVID-19 symptoms

Abstract: Although serological studies have shown that antibodies against SARS-CoV-2 play an important role in protection against (re)infection, the dynamics of mucosal antibodies during primary infection and their potential impact on viral load and the resolution of disease symptoms remain unclear. During the first pandemic wave, we assessed the longitudinal nasal antibody response in index cases with mild COVID-19 and their household contacts. Nasal and serum antibody responses were analysed for up to nine months. Hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 43 publications
(54 reference statements)
4
67
0
Order By: Relevance
“…Froberg et al [40] recently reported a significant increase in nasal antibody levels in response to COVID-19 acute infection, with similar kinetics as described for the serum and saliva. Nevertheless, as the nasal immune response induced by the SARS-CoV-2 vaccine has not yet been studied, the standard method for antibody quantification in nasal secretions and saliva samples still needs to be further clarified.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Froberg et al [40] recently reported a significant increase in nasal antibody levels in response to COVID-19 acute infection, with similar kinetics as described for the serum and saliva. Nevertheless, as the nasal immune response induced by the SARS-CoV-2 vaccine has not yet been studied, the standard method for antibody quantification in nasal secretions and saliva samples still needs to be further clarified.…”
Section: Discussionsupporting
confidence: 60%
“…The three subjects that had recovered from a severe COVID-19 infection that required hospitalization showed higher levels of circulating and mucosal antibodies in all of the analyzed samples in comparison with subjects with previous mild or pauci-symptomatic infection. This difference between the anti-SARS-CoV-2 antibody levels in subjects with mild and severe infection may probably be ascribed to the different viral load in the two conditions [40,41]. Interestingly, the levels of circulating and mucosal antibodies in subjects with previous mild or pauci-symptomatic infection were comparable to the amount present in the vaccinated population.…”
Section: Discussionmentioning
confidence: 90%
“…Besides, there may be an association between viral load or antibody response or titers, although little research previously attempted to uncover it. While some studies reported that higher Santibody levels are associated with a faster decreased viral load and earlier antibody response [38][39], patients without seroconversion show the lowest viral loads at the other end of the spectrum [39]. It seems that the kinetics of the humoral immune response predicts the speed of viral elimination; for example, the earlier antibody response was associated with a faster viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Memory B cells may be present long after antibodies wane. COVID-19 survivors generate long-lasting mucosal antibodies [ 20 ]. Their role in preventing reinfection remains to be defined.…”
Section: Sars-cov-2 Antibodies In the Diagnosis Of Covid-19mentioning
confidence: 99%